Proceedings of the 28th Australian Conference on Computer-Human Interaction - OzCHI '16 2016
DOI: 10.1145/3010915.3010994
|View full text |Cite
|
Sign up to set email alerts
|

Implications of different feedback types on error perception and psychological reactance

Abstract: In Human Computer Interaction, appropriate feedback is especially important when an error occurs. This work compares implications for user's psychological reactance and acceptance of two different types of error and their representations through feedback. Reactance and acceptance levels were measured after presenting feedback that allows a conclusion on the cause of an occurred error and feedback that fails to do so. It was found that reactance levels were significantly higher and acceptance levels significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Not surprisingly, Ehrenbrink et al found that reactance was higher if the system made errors, compared to when the system did not make errors [5]. What they also found was that errors that were accompanied by adequate feedback, hinting at the error source, produced less reactance in the participants than errors that were accompanied by feedback, not hinting at the error source [5].…”
Section: System Errorsmentioning
confidence: 98%
See 2 more Smart Citations
“…Not surprisingly, Ehrenbrink et al found that reactance was higher if the system made errors, compared to when the system did not make errors [5]. What they also found was that errors that were accompanied by adequate feedback, hinting at the error source, produced less reactance in the participants than errors that were accompanied by feedback, not hinting at the error source [5].…”
Section: System Errorsmentioning
confidence: 98%
“…A similar, but probably not that extreme reaction can also occur in other parts of humancomputer interaction. The phenomenon of reactance has been described in human-computer interaction literature several times [4][5][6][11][12][13][14][15][16][17], but so far there is no general overview on how and when reactance usually takes place in HCI. This is even though reactance can have severe consequences on user acceptance, up to the complete inversion of the desired effect, Figure 1: Screenshot of a video that went viral in 2006 [9] which has already been demonstrated for persuasive health campaigns [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the number of citations, the refined version of HPRS is the most widely used or discussed scale for assessing trait reactance. 1 In recent years, the development of measurement tools has focused on state reactance. Several measurement techniques have been introduced in the literature.…”
Section: Measuring Psychological Reactancementioning
confidence: 99%
“…Reactance is an affective and motivational state of the user. It might result in an unwanted decline of acceptability of a product [1] or less compliance [2]. This work describes the development and introduces a questionnaire that can measure levels of a user's psychological reactance.…”
Section: Introductionmentioning
confidence: 99%